2019
DOI: 10.1002/pssb.201900472
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Oxide Grown by Atomic Layer Deposition: From Heavily n‐Type to p‐Type Material

Abstract: ZnO grown by atomic layer deposition (ALD) is an interesting material for electronic applications requiring low processing temperature. Herein, it is shown that the electrical conductivity of ZnO ALD films can be varied from 10 À1 to 10 2 Ω À1 cm À1 by moving the growth conditions from oxygen rich to zinc rich, through changing the deposition temperature between 100 and 200 C. The temperature-dependent photoluminescence (PL) studies show evidence that shallow defect states in ZnO ALD films are clearly influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 93 publications
1
15
0
Order By: Relevance
“…In detail, the reported hydrogen concentration varies www.advancedsciencenews.com www.pss-a.com from %10 20 to %10 21 at cm À3 in as-grown ZnO films and can be reduced to %10 19 at cm À3 after 3 min of annealing at 800 C. [21] SIMS profiles measured in the present study reveal that the average hydrogen content in the as-grown ZnO samples of the H series varies bewteen %2.5 Â 10 20 and %1.1 Â 10 21 at cm À3 (with the hydrogen profile in the H100 sample shown in Figure 2a) and decreases with increasing growth temperature, as previously reported. [21,31,32] The same trend is observed in the D series for both hydrogen and deuterium, thus indicating that hydrogen residuals originating from both the unreacted metalorganic ligands and -OH groups actually decrease with increasing T g . Furthermore, in this case, the hydrogen concentration is found to be lower, between %5.7 Â 10 19 and %3.5 Â 10 20 at cm À3 , in agreement with DEZn being the only source of hydrogen contamination into the films (see also Figure 2b).…”
Section: Chemical Compositionsupporting
confidence: 65%
See 1 more Smart Citation
“…In detail, the reported hydrogen concentration varies www.advancedsciencenews.com www.pss-a.com from %10 20 to %10 21 at cm À3 in as-grown ZnO films and can be reduced to %10 19 at cm À3 after 3 min of annealing at 800 C. [21] SIMS profiles measured in the present study reveal that the average hydrogen content in the as-grown ZnO samples of the H series varies bewteen %2.5 Â 10 20 and %1.1 Â 10 21 at cm À3 (with the hydrogen profile in the H100 sample shown in Figure 2a) and decreases with increasing growth temperature, as previously reported. [21,31,32] The same trend is observed in the D series for both hydrogen and deuterium, thus indicating that hydrogen residuals originating from both the unreacted metalorganic ligands and -OH groups actually decrease with increasing T g . Furthermore, in this case, the hydrogen concentration is found to be lower, between %5.7 Â 10 19 and %3.5 Â 10 20 at cm À3 , in agreement with DEZn being the only source of hydrogen contamination into the films (see also Figure 2b).…”
Section: Chemical Compositionsupporting
confidence: 65%
“…Growth processes lasted 1500 ALD cycles with an expected ZnO layer's thickness between %220 and 270 nm according to the deposition rates in the ALD growth window. [31,38] The ALD growth parameters were chosen as for ZnO films optimized for high conductivity, [39] i.e., pulsing/purging times were set equal to 40 ms/8 s and 16 ms/22 s for DEZn and water precursors, respectively. www.advancedsciencenews.com www.pss-a.com…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that the ZnO films were deposited on both substrates together during the same ALD process. The series of samples were obtained at temperatures, T g , of 100, 130, 160, 200, 250, and 300 • C. It was shown that, in this T g range, the stoichiometry of the deposited ZnO films changes from O-rich (at 100 • C) to Zn-rich (at 200 • C and above) [6,18]. The thickness of the ZnO/Si layers (100-150 nm) was measured with a reflectometer using a NanoCalc 2000 (Mikropack GmbH, Ostfildern, Germany), and the thickness of the ZnO/a-Al 2 O 3 films (100 nm) was measured with a profilometer (Dektak 6M stylus, Veeco, Tucson, AZ, USA).…”
Section: Growth Details and Used Experimental Techniquesmentioning
confidence: 99%
“…However, recent investigations strongly suggest that hydrogen impurity in ZnO material may be involved in a number of complexes with native point defects, such as V Zn •nH, Zn i •V O •H, and others [2][3][4][5][11][12][13][14]. Some of these complexes introduce shallow donor and acceptor levels that affect the resulting ZnO conductivity [4,10,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…305,306 Despite its intrinsic advantages, the lack of control over dopants and defects hindered its further application to practical devices, thus stimulated a boom over investigating the defect chemistry in ZnO. 302,[307][308][309][310] The as-grown ZnO crystals normally exhibit n-type conductivity, which was initially attributed to the native defects such as Zn interstitials, Zn vacancies or V O (Fig. 12a).…”
Section: Wide Bandgap Oxide Semiconductorsmentioning
confidence: 99%